PSTK exerts protective role in cisplatin‐tubular cell injury via BAX/BCL2/Caspase3 pathway - Yifan Wu; Yuanyuan Xv; Limei Zhao; Ziqi Zhou; Miaomiao Wang; Jima Xi; Ying Liming; Jianling Gao; Bingqing Deng; Dong Zheng (Physiological Reports)
Abstract Cisplatin is a widely used anticancer drug, but its accumulation in renal tubular epithelial cells (TECs) can cause acute kidney injury. Phosphoseryl‐tRNA kinase (PSTK) is an intermediate product produced under oxidative stress conditions. This study aimed to elucidate whether PSTK could protect TECs and its possible mechanisms. We found that PSTK levels decreased after cisplatin treatment, but PSTK overexpression using lentivirus vectors protected TEC viability. Overexpression of PSTK increased selenoprotein concentrations and reduced intracellular ROS levels. Additionally, PSTK overexpression inhibited the BAX/BCL2/Caspase 3 pathway after cisplatin stimulation, suggesting its potential role in preventing cell apoptosis. Taken together, this study suggests that PSTK could protect TEC viability from cisplatin‐induced injury, possibly by inhibiting mitochondrial apoptosis. The study is significant for developing therapeutic strategies that could manipulate PSTK to delay AKI progression.